Visualization of the Membranous Labyrinth and Nerve Fiber Pathways in Human and Animal Inner Ears Using MicroCT Imaging - Glueckert, Rudolf; Johnson Chacko, Lejo; Schmidbauer, Dominik; Potrusil, Thomas; Pechriggl, Elisabeth J.; Hoermann, Romed; Brenner, Erich; Reka, Alen; Schrott-Fischer, Anneliese; Handschuh, Stephan (Frontiers in Neuroscience, 2018)
Design and implantation of bionic implants for restoring impaired hair cell function relies on accurate knowledge about the microanatomy and nerve fibre pathways of the human inner ear and its variation. Non-destructive isotropic imaging of soft tissues of the inner ear with lab-based microscopic X-ray computed tomography (microCT) offers high resolution but requires contrast enhancement using compounds with high X-ray attenuation. We evaluated different contrast enhancement techniques in mice, cat and human temporal bones to differentially visualize the membranous labyrinth, sensory epithelia and their innervating nerves together with the facial nerve and middle ear. Lugol`s iodine potassium iodine (I2KI) gave high soft tissue contrast in ossified specimens but failed to provide unambiguous identification of smaller nerve fibre bundles inside small bony canals. Fixation or post-fixation with osmium tetroxide followed by decalcification in EDTA provided superior contrast of for nerve fibres and membranous structures. We processed 50 human temporal bones and acquired microCT scans with 15µm voxel size. Subsequently we segmented sensorineural structures and the endolymphatic compartment for 3D representations to serve for morphometric variation analysis. We tested higher resolution image acquisition down to 3.0µm voxel size in human and 0.5µm in mice, which provided a unique level of detail and enabled us to visualize single neurons and hair cells in the mouse inner ear, which could offer an alternative quantitative analysis of cell numbers in smaller animals. Bigger ossified human temporal bones comprising the middle ear and mastoid bone can be contrasted with I2KI and imaged in toto at 25µm voxel size. These data are suitable for surgical planning for electrode placements. A preliminary assessment of geometric changes through tissue processing resulted in 1.6% volume increase caused during decalcification by EDTA and 0.5% volume increase caused by partial dehydration to 70% ethanol, which proved to be the best mounting medium for microCT image acquisition.